Sorafenib induced radiation recall dermatitis after spine radiosurgery - Robbins, Jared (J Radiosurg SBRT, 2011)
Radiation recall dermatitis has been documented to occur in previously irradiated skin (within the radiation port) the administration of some chemotherapeutic agents. Clinically, it can occur weeks or months after radiation therapy, and resembles the appearance of acute radiation skin reaction. The patterns of the reaction correspond with radiation fields and skin doses. We report a case of recall dermatitis 8 weeks after of spine radiosurgery initiated by the use of a multi-targeted tyrosine kinase inhibitor, Sorafenib, used for treatment of hepatocellular carcinoma.